Assessment of the Effects of Economic Sanctions on Iranians' Right to Health by Using Human Rights Impact Assessment Tool: A Systematic Review - Fatemeh Kokabisaghi (Kerman University of Medical Sciences, 2018)
Background Over the years, economic sanctions have contributed to violation of right to health in target countries. Iran has been under comprehensive unilateral economic sanctions by groups of countries (not United Nations [UN]) in recent years. They have been intensified from 2012 because of international community's uncertainty about peaceful purpose of Iran's nuclear program and inadequacy of trust-building actions of this country. This review aimed to identify the humanitarian effects of the sanctions on the right of Iranians to health and the obligations of Iran and international community about it. Methods To assess economic sanction policies and identify violated rights and the obligations of states according to international human rights laws, in this study, Human Rights Impact Assessments (HRIA) tool is used. Applying this tool requires collection of evidences regarding the situation of rights. To provide such evidence, a systematic review of literature which involved 55 papers retrieved from the web-based databases and official webpages of Iran's government and UN' health and human rights committees and organizations was done. All articles about the consequences of economic sanctions related to nuclear activities of Iran on welfare and health of Iranians published from January 2012 till February 2017 in English and Persian languages were included. Search terms were economic sanctions, embargoes, Iran, welfare, health and medicine. Additional studies were identified by cross checking the reference lists of accessed articles. All selected papers were abstracted and entered into a matrix describing study design and findings, and categorized into a framework of themes reflecting the areas covered (health and its determinants). According to HRIA framework, related obligations of Iran and other states about adverse effects of the sanctions on Iranians' right to health were extracted. Results The sanctions on Iran caused a fall of country's revenues, devaluation of national currency, and increase of inflation and unemployment. These all resulted in deterioration of people's overall welfare and lowering their ability to access the necessities of a standard life such as nutritious food, healthcare and medicine. Also, the sanctions on banking, financial system and shipment led to scarcity of quality lifesaving medicines. The impacts of sanctions were more immense on the lives of the poor, patients, women and children. Humanitarian exemptions did not protect Iranians from the adverse effects of sanctions. Conclusion Countries which imposed economic sanctions against Iran have violated Iranians' right to health. International community should have predicted any probable humanitarian effects of sanctions and used any necessary means to prevent it. Furthermore, Iran should have used any essential means to protect people from the adverse effects of sanctions. Now, they should work on alleviation of the negative effects of sanctions. Even though, some of the effects such as disability and death cannot be compensated. In future, before imposition of sanctions, decisions makers should advice an international order to prevent such impacts on targeted countries' populations